MEDIA COMPETENCE AS A COMPONENT OF INSTRUCTIONAL TEACHER TRAINING AND APPROACHES TO ITS DIAGNOSING - V. D. Sharko (Kherson State University, 2012)
The paper analyzes the approaches of scientists to determine the structure of the teacher's media competence, are sanctified by the methodological aspects of media education students in the study of natural sciences, the proposed mechanism of diagnosing readiness for the implementation of the teacher to prepare young people for life in a computerized society.